DECODING FINANCIAL MECHANISMS: IN-DEPTH ANALYSIS OF STOCK MARKET DYNAMICS AND GLOBAL INVESTMENT STRATEGIES - Rusmiyati Rusmiyati; Eni Kriswandari; Ahmad Rizani; Endang Supriatna; Putri Anindyajati (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study meticulously explores the intricate world of financial mechanisms, offering an in-depth analysis of stock market dynamics and global investment strategies. The research employs a comprehensive literature review methodology, synthesizing existing knowledge, theories, and empirical evidence. The investigation unfolds in multiple phases, from delineating research objectives to critically evaluating literature, ensuring a systematic approach. The literature review spans finance, economics, and investment management to provide a well- rounded perspective. Through rigorous inclusion and exclusion criteria, the study maintains the integrity of its sources, focusing on seminal works, empirical studies, and robust theoretical frameworks. Key findings emerge in thematic areas, unraveling the fundamental drivers of stock price movements, exploring the multifaceted realm of global investment strategies, and investigating the impact of regulatory frameworks on market dynamics. The study also delves into the interconnectedness between macroeconomics and finance, emphasizing the symbiotic relationship shaping financial landscapes. The research contemplates the ethical considerations influencing financial decision-making by bridging numerical indicators with human decisions. The influence of technological advancements, linkages between stock market crashes and economic depressions, and behavioral factors in investment decision-making further enrich the findings. The literature review's synthesis underscores the transformative impact of technological advancements on global investment strategies, the discernible correlation between stock market crashes and economic depressions, and the crucial role of behavioral factors in financial markets. Integrating qualitative and quantitative insights becomes paramount for a holistic understanding, emphasizing the need for an ethical framework in economic research. The study concludes with a nuanced comprehension of stock market dynamics and global investment strategies, paving the way for strategic decision- making in the ever-evolving landscape of international finance.